Cycles in natural resources and changes in welfare: analysis of six developing countries - Cassing, James H.; Welss, Jerome C.; Zamalloa, Edgar L. (Universidad del Pacífico, 1988)
​In this paper the authors study, in an empirical way, the consequences of natural resources boom-crisis cycles in the presence of domestic distortions of Ínternational trade. More specifically, a suitable accounting system is developed so as to then analize statistical data from six underdeveloped countries. Some hypothesis on boom-crisis cycles are stated and tested in this light, paying special attention to their effects on the economy's rate of growth, the relative proportion (size) of the government sector, and movements in sectorial product and relative prices.​